Perceptions of Usefulness and Behaviors to Keep Using in the Implementation of Regional Management Information System Applications - Sri Maryati; Muhammad Ichsan Siregar (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to test the successful implementation of the Regional Management Information System (Sistem Informasi Manajemen Daerah—SIMDA) by linking the perceived ease of users mediated by perceptions of behavior to continue to use and benefit. This research is quantitative research with a survey method using a questionnaire at the South Sumatra Provincial Government. Then, the data is processed and analyzed using PLS. From the results of the analysis, it is found that there is no significant influence between the relationship between perceived ease of use and the successful implementation of the Regional Information Management System, but perceptions of usefulness and behaviors to keep using can be strong influence between relationship between perceived ease of use and the successful implementation of system. This research contributes to the decision makers of accounting system developers to consider the factors that encourage system users who can try to participate in realizing the successful implementation of the system itself.